2017
DOI: 10.3892/etm.2017.4553
|View full text |Cite
|
Sign up to set email alerts
|

IGF-1 may predict the severity and outcome of patients with sepsis and be associated with microRNA-1 level changes

Abstract: Abstract. IGF-1 functions as an anti-oxidative stress molecule and some critical patients with sepsis have a lower level of serum IGF-1. However, the association between IGF-1 and the severity or prognosis of sepsis remains unclear. This study aimed to elucidate the relationship between serum IGF-1 levels and the severity and prognosis of sepsis, and the possible mechanism was analyzed. Clinical characteristics of patients with sepsis were recorded and analyzed. Serum IGF-1 levels and micro (mi)RNA-1 levels we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 34 publications
1
10
0
1
Order By: Relevance
“…IGF‐1R activation induces the downstream PI3K/Akt pathway, which can further activate mTOR or inactivate GSK‐3ÎČ. Sepsis‐induced inflammation has been shown to decrease IGF‐1 signalling pathway (Wasnik et al, 2020; Xu et al, 2017). Studies also found that sepsis or TNF‐related weak inducer of apoptosis (TWEAK), a member of the TNF ligand family, decreased Akt and GSK‐3ÎČ phosphorylation to induce skeletal muscle atrophy (Dogra et al, 2007; Li, Liu, & Wang, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…IGF‐1R activation induces the downstream PI3K/Akt pathway, which can further activate mTOR or inactivate GSK‐3ÎČ. Sepsis‐induced inflammation has been shown to decrease IGF‐1 signalling pathway (Wasnik et al, 2020; Xu et al, 2017). Studies also found that sepsis or TNF‐related weak inducer of apoptosis (TWEAK), a member of the TNF ligand family, decreased Akt and GSK‐3ÎČ phosphorylation to induce skeletal muscle atrophy (Dogra et al, 2007; Li, Liu, & Wang, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Both high and low UVR doses induced a transient up‐regulation of IGF‐1 expression in the ORS at day 1 after exposure (Figure a,c), which may be a compensatory response of the HF against UV‐induced oxidative stress . Long‐term effect (day 3 of organ culture) of UVR resulted in decreased expression of IGF‐1 expression in the HF epithelium but only upon irradiation with the high dose (Figure a,c).…”
Section: Resultsmentioning
confidence: 92%
“…Evidence has also been presented of the antioxidant and antiinflammatory effects of IGF-1. It is assumed that its low levels may exacerbate oxidative stress injury in sepsis patients [93][94][95] Another hormone associated with the somatotropic axis is ghrelin. This is a relatively recently discovered hormone that acts on the GH secretagogues receptor (GHS-R) and stimulates the secretion of GH by the pituitary gland [96].…”
Section: Somatotropic Axismentioning
confidence: 99%
“…Evidence has also been presented of the antioxidant and anti-inflammatory effects of IGF-1. It is assumed that its low levels may exacerbate oxidative stress injury in sepsis patients [ 93 , 94 , 95 ]…”
Section: Endocrine Disorders In the Course Of Sepsismentioning
confidence: 99%